2012
DOI: 10.1016/j.ijgo.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

From safe motherhood, newborn, and child survival partnerships to the continuum of care and accountability: Moving fast forward to 2015

Abstract: The present paper provides an overview of the Safe Motherhood Initiative, Healthy Newborn Partnership, and Child Survival Partnership and their eventual merge into the Partnership for Maternal, Newborn and Child Health (PMNCH) in 2005. The promise and past successes of the PMNCH are highlighted, with a particular focus on the PMNCH's partner-centric approach showing the importance of collaboration for progress. The aims of the strategic framework for 2012-2015 are presented within the context of the Global Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…1,2 The priority accorded to reductions in maternal mortality is shown by its choice as one of the eight Millennium Development Goals (MDGs). Despite these efforts and visibility, there was broad concern that little or no progress was being made, which prompted intensified efforts by the UN Secretary General through the launch of Every Woman Every Child in 2010, and the subsequent creation of the Commission on Information and Accountability for Women’s and Children’s Health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The priority accorded to reductions in maternal mortality is shown by its choice as one of the eight Millennium Development Goals (MDGs). Despite these efforts and visibility, there was broad concern that little or no progress was being made, which prompted intensified efforts by the UN Secretary General through the launch of Every Woman Every Child in 2010, and the subsequent creation of the Commission on Information and Accountability for Women’s and Children’s Health.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these efforts and visibility, there was broad concern that little or no progress was being made, which prompted intensified efforts by the UN Secretary General through the launch of Every Woman Every Child in 2010, and the subsequent creation of the Commission on Information and Accountability for Women’s and Children’s Health. 2,3 In 2010, a comprehensive assessment of global trends in maternal mortality suggested that the maternal mortality ratio (MMR; number of maternal deaths per 100 000 livebirths) had decreased by 1·3% per year since 1990. 4 Subsequent revisions of the historical estimates have shown even larger worldwide rates of change, from −1·9% to −3·1% per year.…”
Section: Introductionmentioning
confidence: 99%
“…Flavia Bustreo, the Partnership’s director from 2006 to 2010, has argued that ‘the potential of the PMNCH to unify the previously fragmented maternal, newborn and child health (MNCH) communities created a positive atmosphere and sparked productive collaborations across sectors and constituencies’ (Bustreo et al 2012, p. S7). The increased visibility of the ‘MNCH’ agenda, she argues, helped promote a ‘continuum of care’ approach in maternal, newborn and child health care initiatives, thereby fostering greater appreciation for integrated health systems thinking (Bustreo et al 2012, p. S7).…”
Section: Introductionmentioning
confidence: 99%
“…These relate to the relative emphasis on comprehensive versus selective approaches to health and the role of long-term health system development versus the pursuit of magic bullets. Despite recent claims that the PMNCH is ‘a testament to growing emphasis on collaboration as the most effective way forward to improving the lives of women, newborn and children’ (Bustreo et al 2012, p. 8), we explore how the politics of institutional control and distinct advocacy coalitions’ tendency towards competition for funding and attention have posed a challenge to effective collaboration—or partnership—between expert groups. We end by reflecting on whether the current partnership model that dominates global health governance is equipped to meet the challenges of achieving institutional and programmatic integration.…”
Section: Introductionmentioning
confidence: 99%
“…1 In general, maternal health have become a priority in MDGs, decanted as the fifth item (MDGs 5), that is to "improve quality of maternal health". 2,3 In the April 2011 report, Hernawati et al 4 from Directorate of Maternal Health Ministry of Health Republic of Indonesia, mentioned that maternal mortality in Indonesia, based on Basic Health Survey called "Riskesdas" latest data on 2007, was 228 per 100.000 live births.…”
Section: Methodsmentioning
confidence: 99%